Mikrotik-based Firewall as a Filter Site Blocking in Pahunga Lodu Secretariat - Meyfrita Hada Indah Nggandung; Fajar Hariadi; Novem Berlian Uly (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The rapid development of information technology has had a significant impact on various aspects of life, including the government agency environment. One of the challenges faced is the misuse of internet access by employees, which can reduce work productivity, such as accessing online gambling sites and adult content. This study was conducted at the Pahunga Lodu Subdistrict Secretariat with the aim of analyzing the effectiveness of implementing a MikroTik-based firewall in blocking access to websites irrelevant to work activities. The method used involved configuring the firewall on the MikroTik RouterOS device with features such as Web Filtering, DNS Filtering, and Layer 7 Protocol. Data collection was conducted through direct observation of network activity before and after the implementation of the firewall, as well as interviews with employees regarding its impact on work productivity. Additionally, testing was performed using Quality of Service (QoS) parameters such as throughput, packet loss, delay, and jitter to assess network performance after the system implementation. The results of the study indicate that the MikroTik firewall is effective in blocking access to unwanted websites and helps maintain stability and efficiency in bandwidth usage. Based on interviews, the majority of employees support the implementation of this system because it has a positive impact on the work environment. This study contributes to improving network security and work efficiency in the government environment and can serve as a reference for the implementation of similar technologies in other institutions. The implementation of web filtering also has a positive impact on overall network quality. A 10-minute test showed an improvement in Quality of Service (QoS) parameters, with throughput increasing from 335.60 kbps to 380.16 kbps (+44.56 kbps), packet loss decreasing from 2.76% to 1.64% (−1.12%), delay decreased from 13.7 ms to 12.2 ms (−1.5 ms), and jitter decreased from 16.93 ms to 12.15 ms (−4.78 ms).